LA PROBLEMÁTICA CHANKA: ANÁLISIS SOCIOPOLÍTICO DE LAS SOCIEDADES TARDÍAS DE LA SIERRA CENTRO SUR ANDINA - Dalen Luna, Pieter D. van (2017)
It presents a view on the prehispanic archeology of the Peruvian southeastern center, commonly called “Chanka”, in which numerous socio-political entities were developed; Some facing each other, while others interacted socially and culturally. The Tawantinsuyu conquered these territories after the defeat of the Chankas in Cusco, for which some of the neighbors of the Chankas (like the Quichuas), allied themselves with the expansive state cusqueño. Based on the review of the data, the development territory of the Chankas was the present province of Andahuaylas and not the current region of Ayacucho.